Motivation and Perceived Learning of Secondary Education History Students. Analysis of a Programme on Initial Teacher Training - Gómez Carrasco, Cosme J.; Rodríguez-Medina, Jairo; Miralles-Martínez, Pedro; López-Facal, Ramón (Frontiers in Psychology, 2021)
This paper presents the results of research on the initial teacher training in Spain. The aim is to verify whether the development of a training program for teachers based on methodological and epistemological aspects has a positive repercussion on the learning of secondary school pupils. We evaluated to what degree this training was reflected in secondary education pupils (n=467) taught by the participating trainee teachers during their period of teaching practice. A pretest and a postest were employed to obtain data on the methodology and the motivation and perceived learning on the part of the pupils. A factor analysis was carried out in order to verify the validity and internal consistency of the tools and, later, the longitudinal invariance in each of the dimensions analysed. The results confirm the internal consistency and validity of the tools employed and the improvement in the pupils’ evaluation regarding methodology, motivation and learning.